High-strength para-aramid fiber and preparation method thereof
By introducing the synergistic effect of graphene oxide and isopropyltris(dioctylpyrophosphateyloxy)titanate in the preparation process of para-aramid fiber, the problem of insufficient mechanical properties of para-aramid fibers is solved, and the preparation of high-strength para-aramid fibers is realized, meeting the needs of higher mechanical properties.
Patent Information
- Application Number
- CN202411988245.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing para-aramid fibers have shortcomings in mechanical properties and cannot meet higher application needs.
Under nitrogen protection, graphene oxide and anhydrous lithium chloride were dissolved in anhydrous N-methylpyrrolidone, added p-phenylenediamine and terephthalyl chloride, and carried out in situ polymerization to obtain a spinning liquid, and was spinned by dry spray wet method, followed by immersion in acetone solution of isopropyl tris(dioctylpyrophosphateyloxy)titanate, and ultrasonic treatment and high-temperature tensile treatment to obtain high-strength para-aramid fiber.
The tensile strength and elongation of break of paraaramid fibers are improved, and the demand for higher mechanical properties is met. The tensile strength is ≥26cN/dtex, and the elongation of break is 3.7% to 4.0%.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aramid fiber materials, and in particular, relates to a high-strength para-aramid fiber and a preparation method thereof. Background Art
[0002] Aramid fibers are mainly divided into three types: meta-aramid, para-aramid and heterocyclic aramid. Para-aramid, namely poly(p-phenylene terephthalamide) (PPTA), is a fully para-polyaramid formed by the condensation polymerization of para-phenylene diamine and terephthaloyl chloride. Thanks to the conjugation of a large number of benzene rings and amide groups, the PPTA molecular chain segments are difficult to rotate internally and present a rod-like structure. The macromolecular chain shows a high degree of order, which perfectly meets the straight chain structure of high-performance fibers. Para-aramid is widely used in the fields of optical fiber reinforcement, safety protection, rubber reinforcement and anti-friction. However, with the progress of society, the above-mentioned application fields have put forward higher requirements on the mechanical properties of para-aramid fibers. Due to the internal defects of para-aramid fibers themselves, their mechanical properties cannot meet the use requirements. Therefore, it is of great significance to develop a preparation method for high-strength para-aramid fibers. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0004] In order to achieve these purposes and other advantages of the present invention, a method for preparing high-strength para-aramid fiber is provided, comprising the following steps:
[0005] Step 1: Under nitrogen protection, dissolve graphene oxide and anhydrous lithium chloride in anhydrous N-methylpyrrolidone, cool to 5-15°C, add p-phenylenediamine, stir until completely dissolved, cool to -10-0°C, add terephthaloyl chloride, stir for 20-40 minutes, warm to room temperature, continue stirring for 1-3 hours, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, mix with sulfuric acid, degas, filter, and obtain a spinning solution;
[0006] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding;
[0007] Step 3: immerse the para-aramid fiber obtained in step 2 in an acetone solution of isopropyl tri(dioctyl pyrophosphate) titanate, perform ultrasonic treatment, wash with acetone and deionized water in sequence, vacuum dry, and perform high-temperature constant tension treatment to obtain high-strength para-aramid fiber.
[0008] Preferably, in step 1, the number of graphene oxide layers is 1 to 3, and the particle size is 100 nm to 1 μm.
[0009] Preferably, in step 1, the mass ratio of graphene oxide, anhydrous lithium chloride and anhydrous N-methylpyrrolidone is 0.05-0.2:4-6:80-200.
[0010] Preferably, in the step 1, the mass ratio of graphene oxide to p-phenylenediamine is 0.05-0.2:3.
[0011] Preferably, in the step 1, the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1 to 1.02.
[0012] Preferably, in step 1, the concentration of sulfuric acid is 98-100 wt %; and the mass ratio of the solid product to sulfuric acid is 1:3-6.
[0013] Preferably, in the step 2, the specific process parameters of spinning are: the coagulation bath temperature is 3°C, the coagulation liquid used is 2-8wt% sulfuric acid aqueous solution, the draft ratio is 4-8, 5-15°C deionized water washing, pH 8-10 calcium hydroxide solution alkaline washing, drying temperature 100-200°C, spinning speed 200-400m / min.
[0014] Preferably, in step three, the power of the ultrasonic treatment is 200-400 W, the frequency is 60-80 kHz, and the time is 1-3 h.
[0015] Preferably, in the step 3, the concentration of isopropyl tri(dioctyl pyrophosphate) titanate in the acetone solution of isopropyl tri(dioctyl pyrophosphate) titanate is 1 to 6 wt %.
[0016] Preferably, in step three, the high temperature constant tension treatment is specifically: treating at 300-350° C. and 1.0-1.2 cN / dtex tension for 3-5 min in a nitrogen atmosphere.
[0017] Preferably, in the step 1, modified graphene oxide is used to replace graphene oxide; the preparation method of the modified graphene is: dispersing graphene oxide in anhydrous ethanol, adding polyvinyl pyrrolidone K20 and polyethylene glycol diamine (M w =2000), ultrasonically treating at 20-50°C, 100-400W, 40-60kHz for 0.5-2h to obtain a dispersion; adding calcium chloride to the dispersion, maintaining stirring, heating to 50-70°C, keeping warm for 0.5-2h, standing for 10-24h, evaporating to remove the solvent, and vacuum drying to obtain modified graphene oxide; wherein the mass volume ratio of graphene oxide, polyvinyl pyrrolidone K20, polyethylene glycol diamine, calcium chloride and anhydrous ethanol is 1g:0.1-0.3g:0.1-0.5g:0.05-0.2g:30-60mL.
[0018] A high-strength para-aramid fiber prepared by the preparation method as described above.
[0019] The present invention at least includes the following beneficial effects: the present invention introduces graphene oxide with extremely high mechanical strength into the para-aramid fiber through in-situ polymerization, which can fill the internal defects of the para-aramid fiber and improve the mechanical properties of the para-aramid fiber; at the same time, the present invention uses an acetone solution of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate to perform an impregnation modification treatment on the obtained para-aramid fiber, and then performs a high-temperature constant tension treatment to induce molecular chain rearrangement and crystallization, promote bonding and cross-linking, and the graphene oxide contains abundant oxygen-containing groups such as carboxyl groups, and has a synergistic effect with isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, which further improves the mechanical properties of the para-aramid fiber; in addition, the present invention uses polyvinyl pyrrolidone, polyethylene glycol diamine and calcium chloride to perform surface modification treatment on the graphene oxide, which further improves its dispersibility and uniformity in the system, increases active sites, is conducive to cross-linking with the para-aramid fiber, enhances the synergistic coordination with isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and further improves the mechanical properties of the para-aramid fiber. The tensile strength of the high-strength para-aramid fiber prepared by the invention is ≥26 cN / dtex, and the elongation at break is 3.7%-4.0%.
[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0021] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0022] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0023] In the following examples, the graphene oxide used has 1 to 3 layers and a particle size of 100 nm to 1 μm.
[0024] Example 1
[0025] A method for preparing high-strength para-aramid fiber comprises the following steps:
[0026] Step 1, under nitrogen protection, add 1g of graphene oxide and 50g of anhydrous lithium chloride to 1000g of anhydrous N-methylpyrrolidone, stir evenly, cool to 10°C, add 30g of p-phenylenediamine, stir until completely dissolved, cool to -5°C, add 57g of terephthaloyl chloride, stir at -5°C for 30min, warm to room temperature, continue stirring for 2h, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, and then mix with 98wt% sulfuric acid at a mass ratio of 1:4, degas, filter, and obtain a spinning solution;
[0027] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; wherein the specific process parameters are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 5wt% sulfuric acid aqueous solution, the draft ratio is 6, 10°C deionized water washing, pH 9 calcium hydroxide solution alkali washing, drying temperature is 150°C, and the spinning speed is 300m / min;
[0028] Step 3: Immerse the para-aramid fiber obtained in step 2 in an acetone solution containing 4 wt% isopropyl tri(dioctyl pyrophosphate) titanate, ultrasonically treat it at 300 W and 70 kHz for 2 h, wash it with acetone and deionized water in turn, vacuum dry it, and treat it in nitrogen at 350° C. and a tension of 1.2 cN / dtex for 3 min to obtain a high-strength para-aramid fiber. According to GB / T14344-2008, the tensile strength of the fiber is 26.22 cN / dtex, and the elongation at break is 3.9%.
[0029] Example 2
[0030] A method for preparing high-strength para-aramid fiber comprises the following steps:
[0031] Step 1, under nitrogen protection, add 2g of graphene oxide and 50g of anhydrous lithium chloride to 1000g of anhydrous N-methylpyrrolidone, stir evenly, cool to 10°C, add 30g of p-phenylenediamine, stir until completely dissolved, cool to -5°C, add 57g of terephthaloyl chloride, stir at -5°C for 30min, warm to room temperature, continue stirring for 2h, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, and then mix with 98wt% sulfuric acid at a mass ratio of 1:4, degas, filter, and obtain a spinning solution;
[0032] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; wherein the specific process parameters are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 5wt% sulfuric acid aqueous solution, the draft ratio is 6, 10°C deionized water washing, pH 9 calcium hydroxide solution alkali washing, drying temperature is 150°C, and the spinning speed is 300m / min;
[0033] Step 3: Immerse the para-aramid fiber obtained in step 2 in an acetone solution containing 1 wt% isopropyl tri(dioctyl pyrophosphate) titanate, ultrasonically treat it at 300 W and 70 kHz for 2 h, wash it with acetone and deionized water in turn, vacuum dry it, and treat it in nitrogen at 300°C and a tension of 1.0 cN / dtex for 5 min to obtain a high-strength para-aramid fiber with a tensile strength of 26.00 cN / dtex and an elongation at break of 3.8%.
[0034] Example 3
[0035] A method for preparing high-strength para-aramid fiber comprises the following steps:
[0036] Step 1, under nitrogen protection, add 0.5g of graphene oxide and 50g of anhydrous lithium chloride to 1000g of anhydrous N-methylpyrrolidone, stir evenly, cool to 10°C, add 30g of p-phenylenediamine, stir until completely dissolved, cool to -5°C, add 57g of terephthaloyl chloride, stir at -5°C for 30min, warm to room temperature, continue stirring for 2h, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, and then mix with 98wt% sulfuric acid at a mass ratio of 1:4, degas, filter, and obtain a spinning solution;
[0037] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; wherein the specific process parameters are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 5wt% sulfuric acid aqueous solution, the draft ratio is 6, 10°C deionized water washing, pH 9 calcium hydroxide solution alkali washing, drying temperature is 150°C, and the spinning speed is 300m / min;
[0038] Step 3: Immerse the para-aramid fiber obtained in step 2 in an acetone solution containing 6 wt% isopropyl tri(dioctyl pyrophosphate) titanate, ultrasonically treat it at 300 W and 70 kHz for 2 h, wash it with acetone and deionized water in turn, vacuum dry it, and treat it in nitrogen at 350°C and a tension of 1.2 cN / dtex for 3 min to obtain a high-strength para-aramid fiber with a tensile strength of 26.15 cN / dtex and an elongation at break of 3.7%.
[0039] Example 4
[0040] In this embodiment, modified graphene oxide is used to replace graphene oxide, and the remaining steps are the same as those in Embodiment 1 to obtain a high-strength para-aramid fiber with a tensile strength of 27.95 cN / dtex and an elongation at break of 4.0%;
[0041] The preparation method of modified graphene is as follows: 10g of graphene oxide is dispersed in 500mL of anhydrous ethanol, 2g of polyvinyl pyrrolidone K20 and 2g of polyethylene glycol diamine (M W =2000), ultrasonically treat at 40°C, 300W, 50kHz for 1h to obtain a dispersion; add 1g of calcium chloride to the dispersion, maintain stirring, heat to 60°C, keep warm for 1h, let stand for 12h, evaporate the solvent at 40°C, and vacuum dry at 60°C to obtain modified graphene oxide.
[0042] Example 5
[0043] In this embodiment, modified graphene oxide is used to replace graphene oxide, and the remaining steps are the same as those in Example 1 to obtain a high-strength para-aramid fiber with a tensile strength of 27.30 cN / dtex and an elongation at break of 3.9%;
[0044] The preparation method of modified graphene is as follows: 10g of graphene oxide is dispersed in 500mL of anhydrous ethanol, 2g of polyvinyl pyrrolidone K20 and 2g of polyethylene glycol diamine (M W =2000), ultrasonically treat at 40°C, 300W, 50kHz for 1h to obtain a dispersion; maintain stirring, heat the dispersion to 60°C, keep warm for 1h, let stand for 12h, evaporate the solvent at 40°C, and dry in vacuo at 60°C to obtain modified graphene oxide.
[0045] Comparative Example 1
[0046] In this comparative example, graphene oxide was not added, and the remaining steps were the same as those in Example 1. The obtained high-strength para-aramid fiber had a tensile strength of 24.03 cN / dtex and an elongation at break of 3.7%.
[0047] Comparative Example 2
[0048] In this comparative example, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is not used for treatment, and the remaining steps are the same as those in Example 1, specifically:
[0049] Step 1, under nitrogen protection, add 1g of graphene oxide and 50g of anhydrous lithium chloride to 1000g of anhydrous N-methylpyrrolidone, stir evenly, cool to 10°C, add 30g of p-phenylenediamine, stir until completely dissolved, cool to -5°C, add 57g of terephthaloyl chloride, stir at -5°C for 30min, warm to room temperature, continue stirring for 2h, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, and then mix with 98wt% sulfuric acid at a mass ratio of 1:4, degas, filter, and obtain a spinning solution;
[0050] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; wherein the specific process parameters are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 5wt% sulfuric acid aqueous solution, the draft ratio is 6, 10°C deionized water washing, pH 9 calcium hydroxide solution alkali washing, drying temperature is 150°C, and the spinning speed is 300m / min;
[0051] Step 3: Immerse the para-aramid fiber obtained in step 2 in acetone, perform ultrasonic treatment at 300 W and 70 kHz for 2 h, wash with acetone and deionized water in turn, vacuum dry, and then treat in nitrogen at 350° C. and 1.2 cN / dtex tension for 3 min to obtain high-strength para-aramid fiber with a tensile strength of 24.36 cN / dtex and an elongation at break of 3.6%.
[0052] Comparative Example 3
[0053] In this comparative example, 4 wt % isopropyl tri(dioctyl pyrophosphate) titanate ethanol solution was used to replace 4 wt % isopropyl tri(dioctyl pyrophosphate) titanate acetone solution, and the remaining steps were the same as those in Example 1 to obtain high-strength para-aramid fiber with a tensile strength of 25.40 cN / dtex and an elongation at break of 3.8%.
[0054] Comparative Example 4
[0055] This comparative example does not perform high temperature constant tension treatment, and the remaining steps are the same as those in Example 1, specifically:
[0056] Step 1, under nitrogen protection, add 1g of graphene oxide and 50g of anhydrous lithium chloride to 1000g of anhydrous N-methylpyrrolidone, stir evenly, cool to 10°C, add 30g of p-phenylenediamine, stir until completely dissolved, cool to -5°C, add 57g of terephthaloyl chloride, stir at -5°C for 30min, warm to room temperature, continue stirring for 2h, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, and then mix with 98wt% sulfuric acid at a mass ratio of 1:4, degas, filter, and obtain a spinning solution;
[0057] Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; wherein the specific process parameters are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 5wt% sulfuric acid aqueous solution, the draft ratio is 6, 10°C deionized water washing, pH 9 calcium hydroxide solution alkali washing, drying temperature is 150°C, and the spinning speed is 300m / min;
[0058] Step 3: Immerse the para-aramid fiber obtained in step 2 in an acetone solution containing 4 wt% isopropyl tri(dioctyl pyrophosphate) titanate, ultrasonically treat it at 300 W and 70 kHz for 2 h, wash it with acetone and deionized water in turn, and vacuum dry it to obtain a high-strength para-aramid fiber with a tensile strength of 24.81 cN / dtex and an elongation at break of 3.7%.
[0059] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A method for preparing high-strength para-aramid fiber, characterized in that: The following steps are involved: Step 1: Under nitrogen protection, dissolve graphene oxide and anhydrous lithium chloride in anhydrous N-methylpyrrolidone, cool to 5-15°C, add p-phenylenediamine, stir until completely dissolved, cool to -10-0°C, add terephthaloyl chloride, stir for 20-40 minutes, warm to room temperature, continue stirring for 1-3 hours, wash the obtained solid product with deionized water until neutral, vacuum dry, crush, mix with sulfuric acid, degas, filter, and obtain a spinning solution; Step 2, the obtained spinning solution is subjected to dry-jet wet spinning, and the para-aramid fiber is obtained through the process steps of coagulation bath, water washing, alkali washing, drying and winding; Step 3: immerse the para-aramid fiber obtained in step 2 in an acetone solution of isopropyl tri(dioctyl pyrophosphate) titanate, perform ultrasonic treatment, wash with acetone and deionized water in sequence, vacuum dry, and perform high-temperature constant tension treatment to obtain high-strength para-aramid fiber.
2. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 1, the number of graphene oxide layers is 1 to 3, and the particle size is 100 nm to 1 μm; the mass ratio of graphene oxide, anhydrous lithium chloride and anhydrous N-methylpyrrolidone is 0.05 to 0.2:4 to 6:80 to 200.
3. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 1, the mass ratio of graphene oxide to p-phenylenediamine is 0.05-0.2:
3.
4. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 1, the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1 to 1.
02.
5. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 1, the concentration of sulfuric acid is 98-100 wt %; the mass ratio of the solid product to the sulfuric acid is 1:3-6.
6. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 2, the specific process parameters of spinning are: the coagulation bath temperature is 3°C, the coagulation liquid used is a 2-8wt% sulfuric acid aqueous solution, the draft ratio is 4-8, 5-15°C deionized water washing, pH 8-10 calcium hydroxide solution alkaline washing, drying temperature 100-200°C, and spinning speed 200-400m / min.
7. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 3, the power of the ultrasonic treatment is 200-400 W, the frequency is 60-80 kHz, and the time is 1-3 hours.
8. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step 3, the concentration of isopropyl tri(dioctyl pyrophosphate) titanate in the acetone solution of isopropyl tri(dioctyl pyrophosphate) titanate is 1-6 wt %.
9. The method for preparing high-strength para-aramid fiber according to claim 1, characterized in that: In the step three, the high temperature constant tension treatment is specifically: in a nitrogen atmosphere, at 300-350° C. and a tension of 1.0-1.2 cN / dtex for 3-5 minutes.
10. A high-strength para-aramid fiber prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-strength para-aramid fiber and preparation method thereof
CN114351276A
Preparation method of graphene modified high-strength and high-modulus heterocyclic aramid
CN115216857A
High-strength para-aramid fiber and preparation method thereof
CN118727433A
Preparation method of high-modulus para-aramid
CN119083150A
Method of manufacturing copolymerized aramid fiber and copolymerized aramid fiber manufactured thereby
KR1020160072030A
Cited By
Preparation and regulation method of olefinic carbon reinforced phase change aramid fiber
CN121496739A